1991
DOI: 10.1111/j.1399-6576.1991.tb03306.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thoracic epidural anesthesia and adrenoceptor blockade on the cardiovascular response to dopamine in the dog

Abstract: The cardiovascular effects of dopamine are different before and during thoracic epidural anesthesia (TEA). To evaluate underlying adrenoceptor-mediated mechanisms, dopamine effects were investigated in nine chloralose-anesthetized dogs. The circulatory response to dopamine (0-40 micrograms.kg-1.min-1) was studied before and during TEA, and during TEA after introducing the alpha 1-antagonist prazosin (0.3 mg.kg-1), the alpha 2-antagonist rauwolscine (0.3 mg.kg-1), and the beta 1-antagonist metoprolol (0.5 mg.kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
2
2
0
1
Order By: Relevance
“…Thc underlying mechanism for this altered vascular responsiveness of dopamine by isoflurane anesthesia is obscure. In this context it is, however, noteworthy that dopamine-induced systemic vasoconstriction was potentiated after thoracic epidural sympathetic blockade in the dog (33). Similar observations have been made in man (34).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Thc underlying mechanism for this altered vascular responsiveness of dopamine by isoflurane anesthesia is obscure. In this context it is, however, noteworthy that dopamine-induced systemic vasoconstriction was potentiated after thoracic epidural sympathetic blockade in the dog (33). Similar observations have been made in man (34).…”
Section: Discussionsupporting
confidence: 77%
“…Similar observations have been made in man (34). Seemingly, the decrease in sympathetic adrenergic outflow, induced by epidural blockade (33,34) may facilitate the vawular responsivencss to exogenous dopamine. Recent data demonstrate that isoflurane anesthesia is associated with decreases in sympathetic nervous dischargc in man (35).…”
Section: +Isupporting
confidence: 72%
“…Although experimental studies on thoracic epidural analgesia have been reported [6][7][8]13], epidural neuroaxial blocks in the thoracic or cranial lumbar area have rarely been used in the clinical setting. However, a paper documented an easy access at T13-L1 and L1-L2 levels for the injection of a contrast medium for myelography [15]; therefore, we believe that needle insertion and epidural catheterization should be feasible through the cranial lumbar intervertebral spaces.…”
mentioning
confidence: 99%
“…При введении местного анестетика в эпидуральное пространство происходит блокада импульсов симпатических нервов на уровне соответствующих дерматомов. По данным экспериментальных исследований на животных, эффекты выключения влияния симпатической нервной системы на сосудистый тонус могут варьировать -от отсутствия влияния [29] до значимого снижения сосудистого сопротивления [30,31]. При исследовании динамики сосудистого сопротивления у пациентов во время кардиохирургических вмешательств с использованием эпидуральной анестезии было показано, что блокада кардиальных дер-матомов снижает сосудистое сопротивление [32].…”
Section: влияние эпидуральной анестезии на сосудистый тонусunclassified